2017
DOI: 10.1111/medu.13326
|View full text |Cite
|
Sign up to set email alerts
|

Dealing with the tension: how residents seek autonomy and participation in the workplace

Abstract: Tensions arose when supervisors did not give trainees the desired degree of autonomy and opportunities to participate. Trainees responded in various ways to maximise their learning opportunities. For these different engagement-related responses to enhance workplace learning in specialty training, achieving intersubjectivity between trainee and supervisor seems foundational.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
47
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 30 publications
(67 reference statements)
2
47
0
Order By: Relevance
“…This is not surprising, as residents or interns learn, similar to medical students in clinical environments, through work‐related activities and through interpretation of experiences and social interaction . Multiple studies on residents' active learning in clinical contexts have highlighted the importance of scaffolding their learning opportunities to foster their feelings of competence and autonomy, similar to medical students . Other studies have shown additional similarities, such as how residents' active learning in clinical contexts also varies to include both planned and reactive learning, how questions of others (such as the patient) may be strong motivators for goal setting in active learning, and how individualised learning plans may be helpful to support active learning …”
Section: Self‐regulated Lifelong Learning In Medical Educationmentioning
confidence: 99%
“…This is not surprising, as residents or interns learn, similar to medical students in clinical environments, through work‐related activities and through interpretation of experiences and social interaction . Multiple studies on residents' active learning in clinical contexts have highlighted the importance of scaffolding their learning opportunities to foster their feelings of competence and autonomy, similar to medical students . Other studies have shown additional similarities, such as how residents' active learning in clinical contexts also varies to include both planned and reactive learning, how questions of others (such as the patient) may be strong motivators for goal setting in active learning, and how individualised learning plans may be helpful to support active learning …”
Section: Self‐regulated Lifelong Learning In Medical Educationmentioning
confidence: 99%
“…Billett used the term ‘affordances’ to highlight the fact that such situations could be both enabling or restricting in terms of learners’ participation. As a result, engagement in workplace affordances is complex and unpredictable . So much so, that learners that share the same training could end up having completely different learning trajectories, as the experiences they accumulate could vary both in quality and quantity …”
mentioning
confidence: 99%
“…Specific modification of clinical complexity by modifying different dimensions of the environment may generate valuable insights into learning environments that are motivating. Previous studies indicated a mismatch between trainees’ and supervisors’ perceptions of and preferences for trainees’ autonomous practice . In addition, trainees’ preferences for supervisory style seem to change over time, which implies that the relation between supervisory style and trainees’ preferences should be taken into account.…”
Section: Discussionmentioning
confidence: 98%